Значение бизнес-культуры, социальной ответственности в повышении эффективности предпринимательской деятельности - Смоловик, Раиса Федоровна (НТУ "ХПИ", 2017)
В статье рассмотрены основные особенности организации предпринимательской деятельности в сфере обслуживания; требования, предъявляемые к профессиональной подготовке менеджмента и сотрудников, указанных предприятий; отмечена важная роль в организации предпринимательской деятельности социальной ответственности, культуры и философии. Особо подчеркивается, что специалист в области организации, управления производством должен владеть навыками и приемами делового общения; анализа конфликтных ситуаций; уметь с помощью слова убеждать, аргументировать, достигать согласия; осуществлять "психологическую терапию". Умение говорить, быть правильно понятым, слушать и понимать, ненавязчиво убеждать, создавать доверительные отношения, искренне сочувствовать – все это важнейшие характеристики делового общения. Удовлетворять таким требованиям может только тот руководитель, который постоянно совершенствует свои знания, умения, никогда не останавливается на достигнутом.

In the article the basic features of organization of entrepreneurial activity are considered in the field of service; requirements, produced to professional preparation of management and employees, indicated enterprises; an important role is marked in organization of entrepreneurial activity of social responsibility, culture and philosophy. It is especially underlined that a specialist is in area of organization, managements must own a production by skills and receptions of business commonunication; analysis of conflict situations; able by means of word to convince, argue, arrive at a consent; to carry out "psychological therapy". Ability to talk, being is correct to understood, to listen and understand, unobtrusively to convince, create confidence relations, sincerely to sympathize are all major descriptions of business commonunication. A that leader, that perfects the knowledge, abilities constantly, never decides on attained, can satisfy to such requirements only. In this regard, in modern conditions, a specialist in the field of organization and management of the restaurant business must have the skills and techniques of business communication; analysis of conflict situations; to be able to convince, argue, reach agreement with the help of the word; to carry out "psychological therapy". Ability to speak, be correctly understood, listen and understand, gently convince, create trusting relationships, sincerely sympathize – all these are the most important characteristics of business communication.
The importance of business culture, social responsibility in improving business performance
Keywords: этикет; культура предприятия; конкуренция; этические ценности; оплата труда; бизнес; предпринимательство; банкет; деловой прием; менеджер; etiquette; culture of enterprise; competition; ethic values; remuneration of labour; business; social responsibility; enterprise; banquet; business reception; manager